2014
DOI: 10.1186/1744-8069-10-63
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Reverses Central Hypersensitivity and Suppresses Medial Prefrontal Cortical Glucose Metabolism in Rats with Neuropathic Pain

Abstract: BackgroundGabapentin (GBP) is known to suppress neuropathic hypersensitivity of primary afferents and the spinal cord dorsal horn. However, its supra-spinal action sites are unclear. We identify the brain regions where GBP changes the brain glucose metabolic rate at the effective dose that alleviates mechanical allodynia using 18 F-fluorodeoxyglucose-positron emission tomography (FDG-PET) scanning.ResultsComparing the PET imaging data before and after the GBP treatment, the spared nerve injury-induced increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…Furthermore, we found the S1HL area began to cooperate with the AIC under the neuropathic pain condition; however, the overall S1HL activity did not differ between the SNI and sham groups. In our previous study, we observed no variations in S1HL responses to von Frey hair stimulation between SNI and naïve rats [ 34 ]. Whether and how the S1 is involved in allodynia is the subject of debate.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, we found the S1HL area began to cooperate with the AIC under the neuropathic pain condition; however, the overall S1HL activity did not differ between the SNI and sham groups. In our previous study, we observed no variations in S1HL responses to von Frey hair stimulation between SNI and naïve rats [ 34 ]. Whether and how the S1 is involved in allodynia is the subject of debate.…”
Section: Discussionmentioning
confidence: 95%
“…It is important to point out that pharmacokinetics of gabapentin in humans and rodents is different [61], which may explain higher systemic and intrathecal doses used in this and other rodent studies [17; 20; 23; 24; 38; 68]. For intra-rACC injections, we used 10 and 100 μg in anesthetized and awake rats, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We used a dose 5-10 fold higher to account for faster rate of elimination in rats [61; 65]. This dose is based on previous studies that used intraperitoneal or subcutaneous dosing of 100 mg/kg in rats [17; 23; 24; 38] At this dose, gabapentin did not produce sedation [23]. Moreover, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Symptoms may include hypersensitivity to noxious (hyperalgesia) and non-noxious (allodynia) stimuli, as well as spontaneous pain (2). An estimated 7-8% of the general population suffers from mild to moderate forms of neuropathic pain, and 5% may be severely affected by it (3). Such pain is a major health problem that substantially reduces quality of life for the afflicted individuals and poses a significant economic burden to the health system and society (2).…”
Section: Introductionmentioning
confidence: 99%